Distribution of Non Hodgkins Malig-Nant Lymphomas (Lennerts Classification) in S. Paulo-Brasil - Machado, J. C. (2023)
The A.A. present the distribution of the sub-types of the non Hodgkin Malignant Lymphomas (N.H.M.L.) in 71 cases from the Pathology Department of The A. C. Camargo Hospital (São Paulo — Brasil), according with Lennert's (Kiel) classification. Their data are similar with those of Lennert with the exception of L.L.C. (8.1% instead of 20,3%). The N.H.M.L. type B exists in more than 50% of all types. The centroblastomas have almost the same percentage (37% — 30.8%) like the Imunocitomas (18.0% - 16.5%) and Imunoblastossarcomas (13.1% - 12.4%). The A.A. say that the pattern of the Non Hodgkin Lymphoma in São Paulo —Brasil is similar with the european pattern.